Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Section 7.3 - Adding and Subtracting Rational Expressions with the Same Denominator and Least Common Denominator - Exercise Set - Page 507: 10



Work Step by Step

$\frac{x^{2}+9x}{x+7}$-$\frac{4x+14}{x+7}$= $\frac{x^{2}+9x-(4x+14)}{x+7}$= $\frac{x^{2}+9x-4x-14}{x+7}$= $\frac{x^{2}+5x-14}{x+7}$= $\frac{x^{2}+7x-2x-14}{x+7}$= $\frac{x(x+7)-2(x+7)}{x+7}$= $\frac{(x-2)(x+7))}{x+7}$= x-2
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.